Strategi Komunikasi Radio Baladeka Dalam Mempertahankan Pendengar di Era Digital - Azhar Ardiyansyah Maulana; Saepuddin (Jurnal Ilmu Komunikasi, 2025)
The purpose of this study is to determine Radio Baladeka’s communication strategy in retaining listeners in the digital era. This study uses a qualitative descriptive method. Data collection techniques were carried out using observation, documentation, and in-depth interviews. The results of the study show that the communication strategies used by Radio Baladeka are: 1). Conformity strategy: Radio Baladeka adjusts its broadcast schedule and timing to suit the various types and preferences of listeners in accordance with their daily activities. 2). Habit formation strategy is carried out through the selection of appropriate programs in accordance with their format, which are packaged in a consistent broadcast schedule. 3). Listener flow control strategy is implemented in order to maximize listeners from one program to the next. 4). The strategy of storing resources so that Radio Baladeka’s broadcast programs can be used in the future. 5). The strategy of attracting mass resources, Radio Baladeka strives to meet the needs of its listeners by continuing to provide interesting broadcast programs so that it can reach listeners from various backgrounds